To simplify this expression, first combine the like terms with the same variable:
First combine the fractions with the variable \(k\):
\[\dfrac{2}{5}k + \dfrac{1}{10}k = \dfrac{4}{10}k + \dfrac{1}{10}k = \dfrac{5}{10}k = \dfrac{1}{2}k\]
Next, combine the constant fractions:
\[-\dfrac{3}{5} + \dfrac{1}{10} = -\dfrac{6}{10} + \dfrac{1}{10} = -\dfrac{5}{10} = -\dfrac{1}{2}\]
Therefore, the expression simplifies to:
\[\dfrac{1}{2}k - \dfrac{1}{2}\]
{\dfrac{2}{5}k-\dfrac{3}5+\dfrac{1}{10}k}
3 answers
{\dfrac{2}{5}k-\dfrac{3}5+\dfrac{1}{10}k}
To simplify this expression, we start by combining like terms:
First, we combine the terms with \(k\):
\[\dfrac{2}{5}k + \dfrac{1}{10}k = \dfrac{4}{10}k + \dfrac{1}{10}k = \dfrac{5}{10}k = \dfrac{1}{2}k\]
Next, we combine the constant terms:
\[-\dfrac{3}{5} = -\dfrac{6}{10}\]
Now, we can rewrite the expression with simplified terms:
\[\dfrac{1}{2}k - \dfrac{6}{10}\]
We can simplify the constant term further:
\[-\dfrac{6}{10} = -\dfrac{3}{5}\]
Therefore, the simplified expression becomes:
\[\dfrac{1}{2}k - \dfrac{3}{5}\]
First, we combine the terms with \(k\):
\[\dfrac{2}{5}k + \dfrac{1}{10}k = \dfrac{4}{10}k + \dfrac{1}{10}k = \dfrac{5}{10}k = \dfrac{1}{2}k\]
Next, we combine the constant terms:
\[-\dfrac{3}{5} = -\dfrac{6}{10}\]
Now, we can rewrite the expression with simplified terms:
\[\dfrac{1}{2}k - \dfrac{6}{10}\]
We can simplify the constant term further:
\[-\dfrac{6}{10} = -\dfrac{3}{5}\]
Therefore, the simplified expression becomes:
\[\dfrac{1}{2}k - \dfrac{3}{5}\]